DISCONNECTING BY CHOICE: A MICRO-NETNOGRAPHIC STUDY OF SMARTPHONE-TO-FEATURE PHONE MIGRATION FOR DIGITAL DETOX - Suryawan, Tjokorda Gde Agung Wijaya Kesuma (International Journal of Business and Information Technology, 2025)
In an era marked by hyperconnectivity and digital saturation, this study explores the phenomenon of feature phone adoption as a form of digital detox among Indonesian users. Drawing on a micro-netnographic methodology, the research analyses user-generated commentary on a high-engagement Instagram post by a verified media outlet, examining the discursive meanings and affective tensions underpinning the rejection of smartphones. Unlike temporary digital fasting or app-based self-regulation, the adoption of low-tech devices represents a more radical, embodied, and symbolically charged act of consumer resistance. Thematic analysis reveals that this behavioural shift is driven by emotional exhaustion, a desire for cognitive clarity, and a search for authenticity in digitally saturated environments. By foregrounding culturally situated narratives from a mobile-first emerging market, the study challenges dominant techno-optimist assumptions and contributes to theoretical conversations on digital minimalism, anti-consumption, and youth technology cultures. The findings offer both conceptual insight and practical implications for international marketers, particularly in designing psychologically attuned and culturally resonant strategies within emotionally fatigued digital landscapes. This research advances a more nuanced understanding of technological agency, centred not solely on innovation and access, but on intentional disconnection and value-based simplicity.